HUBUNGAN DUKUNGAN SUAMI DENGAN PENGAMBILAN KEPUTUSAN PEMAKAIAN KB IUD DI TPMB SUNARSIH YUDAWATI KECAMATAN WAGIR KABUPATEN MALANG - Lestari, Eka Rahayu Puji (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
The family planning program does not only aim to control the rate of population growth, but also to meet people's demands for quality family planning and reproductive health (KR) services, reduce maternal mortality (AKI) and infant mortality (IMR) as well as tackle reproductive health problems to form quality family. The aim of the study was to determine the relationship between husband's support and decision making for IUD use at TPMB Sunarsih Yudawati. Data analysis is an analysis process that is carried out systematically on the data that has been collected with the aim that trend relationships can be detected. As previously stated, this research is a type of experimental research by comparing two groups of research subjects. The results of research on the relationship between husband's support and decision-making about the use of IUD contraception at TPMB Sunarsih Yudawati Wagir, it can be concluded that: The t value of the variable husband's support (X) is 9.148 > t table 2.045, meaning that there is a significant relationship between husband's support (X) by making decisions on the use of IUD contraception (Y). The calculated F value is 83,687 > from the F value of 0.05 (4.20) meaning that there is a significant relationship simultaneously or simultaneously between the husband's support variable (X) and the decision making of using IUD contraception (Y). The R square value of 0.749 means that the relationship between husband support and decision making for IUD use has a percentage of 74.9%, while the other 25.1% is influenced by other factors not examined in this study.